Pengaruh Perencanaan dan Kompetensi Sumber Daya Manusia terhadap Tingkat Penyerapan Anggaran - Rizka Sri Wandari; Arwan Gunawan; Darya Setia Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
One of the important things in increasing budget absorption is budget planning and the competence of human resources. The budget is used to ensure that the government has implemented and is responsible to the society, but in reality there are still problems such as low budget absorption in the early quarter and piling up in the final quarter thus the budget absorption does not match the ideal limit of budget absorption that has been set. The objective of this research is to examine the effect of budget planning and the competences of human resource either simultaneously or partially on SKPD at Cimahi City government area. Quantitative method was used in this research. The analytical method used in this research was multiple linear regression to test the effect of two or more independent variables toward dependent variable from the data that conducted by distributing questionnaires. The respondents were 76 people, that are the Budget User Authority, the Expense Treasurer, and the Head of the Program and Finance Subdivision at the SKPD in the Cimahi City government area. The data analysis in this study was conducted by using the SPSS For Windows version 26.0 software. It begins with testing the research instrument by testing the validity and reliability then testing the classical assumptions. Hypothesis testing used F test for simultaneous effect and t test for partial effect. The results of this research indicate that budget planning and human resource competence have a positive and significant effect either partially or simultaneously on the level of budget absorption in Cimahi City.